(untitled) (Amsterdam, 2007)
The right to share in scientific advancement and its benefits was enshrined in Article 27 of the Universal Declaration of Human Rights. It was included in the International Covenant on Economic, Social and Cultural Rights (Article 15 , 1 b). Nevertheless, it is generally agreed that the REBSP is an "underdeveloped" human right. No comprehensive study and analysis have been conducted while little reference has been made to it in State reports to the Committee on Economic, Social and Cultural Rights.
Keywords: Human rights,Right to education,Science,Quyền được giáo dục,Quyền con người,Khoa học; International cooperation,Hợp tác quốc tế